2014
DOI: 10.1002/2014rs005404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic storm effects on the variation of TEC over Ilorin an equatorial station

Abstract: We have used total electron content (TEC) derived from dual-frequency GPS receivers to study magnetically quiet and storm time variations of the ionosphere at Ilorin(8.47°N, 4.68°E), an equatorial station in the African sector. Four years (2009)(2010)(2011)(2012) data were used for the study. The result on the quiet time variation of the ionosphere showed that the diurnal variation of TEC is not symmetrical about noon. This is a departure from a typical Chapman variation. Daytime maximum occurred after local n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is understood that the F region in the equatorial latitude is highly influenced by electrodynamics even during quiet time disturbance periods (Buonsanto, , and references therein). The zonal electric fields on the equatorial ionosphere control vertical plasma transport in the low‐latitude ionosphere and drives the equatorial ionization anomalies and causes vertical drifts (Adeniyi et al, ; Shume et al, ). As reported extensively, dayside P ionospheric storm effects in equatorial regions are sometimes related to PPEF (Huang et al, ; Klimenko & Klimenko, ; Mannucci et al, ; Tsurutani et al, , ) and may depend on the strength of PPEF (Balan et al, ).…”
Section: Overall Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is understood that the F region in the equatorial latitude is highly influenced by electrodynamics even during quiet time disturbance periods (Buonsanto, , and references therein). The zonal electric fields on the equatorial ionosphere control vertical plasma transport in the low‐latitude ionosphere and drives the equatorial ionization anomalies and causes vertical drifts (Adeniyi et al, ; Shume et al, ). As reported extensively, dayside P ionospheric storm effects in equatorial regions are sometimes related to PPEF (Huang et al, ; Klimenko & Klimenko, ; Mannucci et al, ; Tsurutani et al, , ) and may depend on the strength of PPEF (Balan et al, ).…”
Section: Overall Statisticsmentioning
confidence: 99%
“…Adewale et al () showed that the positive ionospheric storm effects were more prevalent than negative ionospheric responses during the geomagnetic storm periods between April 2000 and November 2007 using TEC observed at Libreville, Gabon (0.35°N, 9.67°E; 8.05°S, geomagnetic). During the storm period of 2009–2012, Adeniyi et al () used TEC over Ilorin (8.47°N, 4.68°E; 1.84°S, geomagnetic) to study ionospheric dynamic and observed more positive ionospheric response in comparison with negative ionospheric storm effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were made using GPS derived ionospheric data (Obrou et al, 2009;Ouattara et al, 2012;Bolaji et al, 2012;Bolaji et al, 2013;Oladipo et al, 2014;Bolaji et al, 2015), on the solar cycle and the seasonal behavior of TEC (Moeketsi et al, 2007;Ackah et al, 2011;Zoundi et al, 2012;Shimeis et al, 2014), on magnetic storms Adeniyi et al, 2014;De Abreu et al, 2014;Shimeis et al, 2015;Azzouzi et al, 2015). This paper is the first paper in Africa devoted to the IHV of TEC.…”
mentioning
confidence: 99%
“…The seasonal trend observed could be pointing to the fact that the background ionosphere, in addition to the mechanism described above, is equally important in the generation and occurrence of ionospheric irregularities. Many studies including the ones done at Ilorin have shown that the level of ionization is higher during equinox months than during solstice months (e.g., Adeniyi et al, ; Oladipo et al, ). This could explain why the peak of scintillation occurs around March and September at Ilorin.…”
Section: Resultsmentioning
confidence: 99%